Experiences of Modernity: Reading the Female Body in J.G. Sime’s Sister Woman - Mullins, Katie (Studies in Canadian Literature, 2011)
Jessie Georgina Sime’s short story collection Sister Woman (1919) explores a tension between the female body as a site of power and sexual freedom, and the female body as constrained and possessed within patriarchy and the heterosexual matrices of marriage and reproduction. Throughout the collection, characters psychologically and physically confront the social (and bodily) ideals of chastity, purity, cleanliness, and youth. In this way Sime presents the female body as a register of the conflicts of modernity. Reading the body in Sime’s writing allows us to identify strategies in Sime’s writing that allow her to depict the “unsayable” aspects of women’s experience of modernity. Recognising such “embodied” experiences enables an engagement with the complexities and contradictions of modernity as experienced by Sime’s female characters, and invites us to reconsider our critical understanding of subjectivity in Sister Woman.